Determination of reactive oxygen species in myringotomized tympanic membranes: Effect of vitamin E treatment - HAKLAR, GONCAGÜL; YÜKSEL, MERAL; BOZKURT, SÜHEYLA (WILEY, 2004)
Objectives/Hypothesis: Recent studies have established a strong relationship between the development of myringosclerosis and reactive oxygen species (ROS). The aims of the present study were to directly detect ROS in the tympanic membrane and middle ear mucosa of rats by measuring luminol amplified chemiluminescence, to evaluate the changes in the levels of ROS after treatment with vitamin E, and to examine the possible changes in the tympanic membranes otomicroscopically and histologically. Study Design: Prospective controlled animal study. Methods: Forty healthy Sprague-Dawley rats were divided into five groups of eight animals each. Animals in all groups except group 1 were bilaterally myringotomized. Group 2 received no treatment, group 3 was treated with topical olive oil, group 4 received topical vitamin E, and group 5 received intramuscular vitamin E. After 24 hours of myringotomy, tympanic membranes were examined otomicroscopically; thereafter, tympanic membranes and middle ear mucosa were peeled off. The right ears of the animals were used for biochemical assay, and the left ears were used for histological study. Results: Reactive oxygen species levels were significantly decreased in group 4 with topical application of vitamin E compared with untreated and myringotomized animals in group 2. Reactive oxygen species levels were also decreased in group 5, although the decrease was not statistically significant when compared with groups 2 and 3. Histological studies confirmed sclerotic changes in the untreated myringotomized animals. The tympanic membranes of animals in groups 2 and 3 showed a white, chalk-like pattern of sclerotic changes, whereas animals in groups 4 and 5, with the exception of two animals in group 5, lacked these changes. Conclusion: Although the relationship between the development of myringosclerosis and ROS had been well documented previously, the present study is the first that has directly measured the levels of ROS in the tympanic membrane and middle ear mucosa. These results are relevant because they correlate with histological findings. It has also been demonstrated that topically applied vitamin E is effective in decreasing the ROS levels.
Keywords: ACUTE OTITIS-MEDIA; MIDDLE-EAR; GUINEA-PIGS; LIPID-PEROXIDATION; RADICAL INJURY; OLIVE OIL; MYRINGOSCLEROSIS; TYMPANOSCLEROSIS; CHEMILUMINESCENCE; ANTIOXIDANTS